If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -1(-3x + -5) = 5 + -1x Reorder the terms: 8x + -1(-5 + -3x) = 5 + -1x 8x + (-5 * -1 + -3x * -1) = 5 + -1x 8x + (5 + 3x) = 5 + -1x Reorder the terms: 5 + 8x + 3x = 5 + -1x Combine like terms: 8x + 3x = 11x 5 + 11x = 5 + -1x Add '-5' to each side of the equation. 5 + -5 + 11x = 5 + -5 + -1x Combine like terms: 5 + -5 = 0 0 + 11x = 5 + -5 + -1x 11x = 5 + -5 + -1x Combine like terms: 5 + -5 = 0 11x = 0 + -1x 11x = -1x Solving 11x = -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 11x + x = -1x + x Combine like terms: 11x + x = 12x 12x = -1x + x Combine like terms: -1x + x = 0 12x = 0 Divide each side by '12'. x = 0 Simplifying x = 0
| 3e=53 | | 0.4x+12.8=x-2.86 | | x+20y=24 | | K-kx+16=0 | | Twothirds(x+13)=22 | | 7y-8=2y+2 | | 5(x+1.83)=4x | | 3/5x-2/3=4/5 | | -3f+5=14 | | 4(7-2x)-10=6x | | 0.4x+0.1=-1.1 | | x/8=45/10 | | 7(x-6.2)=2.1 | | 4x-2.5+3.8=61 | | 12/.75 | | (x^2)+4+x+30+90=180 | | 11+m=4m-1 | | 8x+8.18=2x+17 | | 2(x+1)+6=10-3x | | (3x-12)+(5x-34)=90 | | (3cosx)*(2cosx)= | | 3x/6=7x-6x/2 | | -4.6x+2.3=-20.7 | | Sin64=16/x | | x+3x-12+5x-34=180 | | -4x-45=39 | | 6x+4y=3.5 | | 3(x+4)-2(2+2x)=3(x-6+12+2) | | 9-2(x+4)=8(3-x)+1 | | -14.3=-1.8-3D | | 5-22=5x-4-4x | | 9×1/1000 |